KAJIAN ALGORITMA CRAIG RAYNOLD PADA KERUMUNAN (FLOCKING) - Ginting, Lit Malem; Siahaan, Binsar; Situmorang, Bastian; Manik, Riris (UNIVERSITAS PELITA HARAPAN, 2018)
Artificial Intelligence (AI) is a study of making computers that do things that today can be done better by humans. One application in the game is to mimic the behavior of animals in the wild. Set of animal in the wild are often called crowds, herds, schools and swarms. Crowds are animals that gather together in an irregular and unfocused way [4]. In 1987, Craig Reynolds [6] with his book